Peningkatan Motivasi Belajar Melalui Pendekatan Bermain pada Pembelajaran PJOK Kelas VI SDN Airlangga 1 Surabaya - Muhammad Faisol; Dony Andrijanto; Luthfi Aidin (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This study proves that the play approach is effective in increasing students' learning motivation in the subjects of Physical Education, Sports, and Health. The results of the study show that through play activities, students are more motivated to actively move and maintain body health. Through classroom action research conducted in two cycles, it was found that the play approach can be an effective solution to increase students' active participation in Physical Education, Sports, and Health learning. Data obtained from observation, documentation, and questionnaires showed a significant increase in learning motivation after the implementation of this approach. The results of this study conclude that the play approach has great potential to increase the interest and motivation of students in grade VI of Airlangga 1 State Elementary School Surabaya in the subjects of Physical Education, Sports, and Health. Therefore, this approach in learning activities is to create a fun and effective learning environment.